Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)
x+(x+1)+(x+2)+....+(x+30)=1240
31 . x + (1 + 2 + 3 + 4 +...+ 29 + 30) = 1240
31 . x + 31.15 = 1240
31 . x = 1240 - 31.15
31 . x = 775
x = 775 : 31
x = 25
b)1 + 2 + 3 +...+ x = 210
(x + 1) . x : 2=210
x . (x + 1) = 420
x . x + x = 420
x . x = 420 - x
Ta thấy:
20 . 20 = 420 - 20
Vậy x = 20
-210=(-1)+(-2)+(-3)+...+(-x+1)+(-x)
=>-(1+2+3+...+x-1+x)=-210
=>1+2+3+...+x-1+x=210
=>x.(x+1):2=210
=>x(x+1)=210.2=420=20.21=20.(20+1)
=>x=20
vậy x=20
-210 = (-1) + (-2) + (-3) + ... + (-x - 1) + (-x)
=> -210 = -(1 + 2 + 3 + ... + x + 1 + x)
=> 210 = 1 + 2 + 3 + ... + x + x + 1
=> 210 = \(\frac{\left(x+1+1\right).\left(x+1\right)}{2}\)
=> 420 = (x + 2) . (x + 1)
=> 21 . 20 = (x + 2) . (x + 1)
=> (19 + 2) . (19 + 1) = (x + 2) + (x + 1)
=> x = 19.